2017
DOI: 10.1002/app.45286
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of nano‐SiO2 reinforced alginate‐based nanocomposite films (II)

Abstract: Crosslinked alginate-based nanocomposites at different SiO 2 contents were prepared successfully by blending the nano-SiO 2 solution into low concentration alginate solution (0.5 wt %), with the alginate concentration increased step by step to the resulted concentration, in this course glycerol was used as plasticizer and 5 wt % CaCl 2 as crosslinker. The combined effect of SiO 2 content (1.5-8 wt %) on the microstructural, physical, mechanical, and optical properties of the nanocomposite films were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…As the SiO 2 concentration increased, it could be seen that the broad peak at 2θ ≈ 13° reduced in intensity, indicating a slight reduction in the crystallinity of the blend film. Similar behavior was observed in the case of incorporating SiO 2 in SA films [ 23 ] and adding montmorillonite clay to these films [ 35 ]. It is noteworthy that, even with the increase in SiO 2 concentration, the typical broad and strong diffraction peak at 2θ ≈ 23° of its amorphous structure was not observed in any of the samples, confirming that there was good filler dispersion along the biopolymer matrix.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…As the SiO 2 concentration increased, it could be seen that the broad peak at 2θ ≈ 13° reduced in intensity, indicating a slight reduction in the crystallinity of the blend film. Similar behavior was observed in the case of incorporating SiO 2 in SA films [ 23 ] and adding montmorillonite clay to these films [ 35 ]. It is noteworthy that, even with the increase in SiO 2 concentration, the typical broad and strong diffraction peak at 2θ ≈ 23° of its amorphous structure was not observed in any of the samples, confirming that there was good filler dispersion along the biopolymer matrix.…”
Section: Resultssupporting
confidence: 74%
“…The incorporation of different SiO 2 concentrations in sodium alginate or pectin films was investigated by evaluating the physical, chemical, and optical properties of the films [ 23 , 24 , 25 ]. Pectin films with SiO 2 showed that nanoparticles can reduce water-vapor permeability by 30–60%, compared to films without nanoparticles [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is cheap and commercially available [82]. Functionalization of polysaccharide using silicon dioxide nanoparticles have received attention due to their high number of silanol groups, and to the ability to form hydrogen bonds with the biopolymer enhancing their technological and functional properties, suitable for food preservation [83][84][85]. Table 5 summarizes the application of polysaccharide-silicon dioxide packaging and their effects on quality parameters of some food products.…”
Section: Silicon Dioxide (Sio 2 )mentioning
confidence: 99%